Abnormal Face‐hand Testing is Associated with Anosognosia in Patients with Neuropathologically‐confirmed Alzheimer’s Disease - Derksen, Brenna (The University of Arizona., 2014)
A Thesis submitted to The University of Arizona College of Medicine - Phoenix in partial fulfillment of the requirements for the Degree of Doctor of Medicine. === Objective To investigate whether specific elements of the neurological and neuropsychological evaluation are associated with anosognosia for memory impairment in subjects with neuropathologically-confirmed Alzheimer’s disease. Methods Included were subjects from the Arizona Study of Aging and Neurodegenerative Disease with clinically documented dementia and neuropathological confirmation of AD for whom anosognosia could be confirmed based on antemortem data. Anosognosia was defined by a discrepancy between 1) the patient’s self-report and results of testing, and/or 2) the patient’s self-report and the caregiver’s report regarding memory impairment. The anosognosic and non-anosognosic groups were compared on targeted clinical, cognitive, and neuropathological findings. Results Of 61 subjects included, 34 were diagnosed as anosognosic, and 27 non-anosognosic. The anosognosic group performed worse on two tests of frontal systems function - letter fluency (COWAT) (p=0.010) and a score derived from the Trailmaking test (Trailmaking B time – Trailmaking A time) (p=0.015). In addition, significantly more anosognosic subjects (92%) had abnormal results on face-hand testing (double simultaneous stimulation) compared to non-anosognosic subjects (62% abnormal; p=0.018). Significance In this study of patients with moderate Alzheimer’s disease (mean CDR=2), the anosognosic group showed significantly greater impairment on tests of frontal/executive function. In addition, this group had a significantly higher rate of abnormal face-hand testing, consistent with right parietal pathology. The FHT, which takes about 30 seconds to administer, may prove useful as a marker for anosognosia risk in AD.